What perceptions do beginning teachers have about the mathematical knowledge they need for teaching? - Clemmet, Claire (2017)
The nature of the professional knowledge that a teacher needs to develop has been the focus of much research in recent decades yet remains contested. This study focuses on the perceptions held by beginning teachers about the mathematical knowledge that they need to be a teacher during the first term of their PGCE mathematics course. There are many conceptual models that set out to categorise the types of knowledge a teacher needs. However, there is less research that explores how beginning teachers view and develop the knowledge that they will need as a teacher. A mixed method case study approach, involving four beginning teachers, traced the development of their perceptions about mathematical knowledge. In agreement with other research, beliefs about mathematics and teaching and learning mathematics were found to be influential in the types of knowledge a beginning teacher prioritised and the approaches they adopted to their own learning. However, their changing identity as a teacher was also significant. Disruptive experiences on the PGCE course challenged the beginning teachers to develop their initial ideas about mathematics and teaching; all involved in this research consequently sought to develop a more connected understanding of mathematics. The challenge to their initial identity as a teacher created much more uncertainty for some than others. This dissertation suggests that development of mathematical knowledge for teaching needs to take place alongside careful consideration of changing identity as a teacher and proposes the use of video reflection as a means to consider this.